Modern Technologies: The Use and Role of Immersive Classroom in Teaching and Learning and its Implications on Educational Management - Sain, Zohaib Hassan (CV. Dalle’ Deceng Abeeayla, 2024)
The role of Artificial Intelligence in reshaping education cannot be under mined. Immersive classroom fueled by evoking classroom technologies such as Virtual Reality, Augmented Reality and Mixed Reality represent a holistic force of transformation offering inclusive dynamic learning experience that prepares not just learners but also educators for the complexities in the digital world. The study of Bailenson et al. (2015) reveals that students who learned through the immersive classroom experiences demonstrated better understanding and retention of concepts compared to their peers who learned using traditional teaching and learning methods. This paper is a contextual review of the use and role of immersive classroom on teaching and learning. The various applications of immersive classroom technologies in teaching and learning were discussed in the paper. The paper also highlighted some of the key benefits and challenges confronting the implementation of immersive classroom technologies in education. Carefully constructed questions were administered to respondents using online Google form questionnaire instrument. The gathered responses were then subjected to reliability analysis. Conclusively, the paper inferred that harnessing the use of immersive technologies we help educators to unlock new dimensions of knowledge and empower learners to thrive in the digital age. Finally, recommendations were made.